PENDAPATAN TENAGA KERJA KELUARGA PADA USAHA TERNAK SAPI POTONG DI KECAMATAN TOROH KABUPATEN GROBOGAN FAMILY LABOUR INCOME ON CATTLE FARMING IN TOROH SUBDISTRICT GROBOGAN REGENCY - Handayani, M.; Gayatri, S.; Mulyatno S, B. (MEDIAGRO, 2005)
This research was done to know the  family labour  income on cattle farming  compare to farmer wage  in there and to know the rentability value compare to rate. Research was done in Juni ± Juli 2004. The method of this research  was  survey, collecting data was done by observation and direct interview. The research was done in Toroh subdistrict Grobogan Regency. Respondents were   52  farmers chose by stratified  random sampling. There were three strata, the first were the farmers who had 1-2 cattle, second had 3-4 cattle and third  had  more  than  4 cattle.   Data was analyzed with descriptive.  The results showed that the  family  labour  income was  higher than farmer  wage.  Family  labour  income in  each  stratum  were  Rp 13.790,67/man-days, Rp 15.966,29/  man-days  and 13.278,95/  man-days respectively, while the farmer  wage  in there was  Rp 12.600/  man-days. Rentability value was higher than  rate.    Rentability in each  stratum were 27.61%, 23.74%, and 24.53% respectively, while the  rate was 12.5%. The conclusion of this research was  that  the cattle  farming  in Toroh Subdistrict was prospectively.   Keywords: family labour income, rentability value